2007
DOI: 10.1021/es0620033
|View full text |Cite
|
Sign up to set email alerts
|

Slightly Weathered Exxon Valdez Oil Persists in Gulf of Alaska Beach Sediments after 16 Years

Abstract: Oil stranded by the 1989 Exxon Valdez spill has persisted in subsurface sediments of exposed shores for 16 years. With annualized loss rates declining from ∼68% yr -1 prior to 1992 to ∼4% yr -1 after 2001, weathering processes are retarded in both sediments and residual emulsified oil ("oil mousse"), and retention of toxic polycyclic aromatic hydrocarbons is prolonged. The n-alkanes, typically very readily oxidized by microbes, instead remain abundant in many stranded emulsified oil samples from the Gulf of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(80 citation statements)
references
References 25 publications
(44 reference statements)
4
76
0
Order By: Relevance
“…1), which was oiled in 1989, was the site of pre-spill collections, and carcass collections were continued there through 2013. Beginning in 1996, in addition to Green Island collections, carcasses were collected from shorelines throughout WPWS that received heavy oiling in 1989, including areas where residual oil was found through at least 2008 (Short and others, 2004(Short and others, , 2006(Short and others, , 2007U.S. Geological Survey, unpub.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1), which was oiled in 1989, was the site of pre-spill collections, and carcass collections were continued there through 2013. Beginning in 1996, in addition to Green Island collections, carcasses were collected from shorelines throughout WPWS that received heavy oiling in 1989, including areas where residual oil was found through at least 2008 (Short and others, 2004(Short and others, , 2006(Short and others, , 2007U.S. Geological Survey, unpub.…”
Section: Methodsmentioning
confidence: 99%
“…In 2001, others (2004, 2006) documented unexpected amounts (>55,000 kg) of Exxon Valdez oil remaining in intertidal habitats in WPWS, and estimated that subsurface oil might persist at some sites for several decades (Short and others, 2007). Studies of mussels and clams, both common prey items of sea otters foraging in intertidal habitats, indicated that lingering oil was bioavailable as late as 2002 (Fukuyama and others, 2000;Thomas and others, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, during post-spill damage assessment studies, the Knight Island complex (Fig. 1) was chosen as a study site because it received heavy oiling in 1989, and the area continued to hold considerable amounts of oil on scattered beaches 20 years after the spill (Short et al 2007). Acute sea otter mortality at the time of the spill approached 90% in this area (Bodkin et al 1993), and sea otter numbers remained reduced through at least 2005 (Supplement; Bodkin et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…On sunny days, turbulent seas and in warm water, photo-oxidation will enhance evaporation and reduce the impact of the WAFs but persistence of the slick, continuously releasing the PAHs, will continue to pose a hazard to aquatic animals especially in subtidal areas (Lee & Page, 1997;Rice et al, 2001;Jewett et al, 2002;Peterson et al, 2003). However, in frigid subarctic waters, decomposition of PAHs will likely progress more slowly than in warmer conditions and, consequently, persist for longer periods as noted following the spill from the Exxon Valdez in Alaska (Jewett et al, 2002;Rice et al, 2007;Short et al, 2007). Oil spilled in the Gulf of Alaska in 1989 still persists after many years in an unweathered state in mussel (Mytilus edulis) beds and in sediment trapped in semi-enclosed bays (Peterson et al, 2003;Rice et al, 2007).…”
Section: Discussionmentioning
confidence: 99%